The effect of a secondary process on crystallization kinetics – Poly (є-caprolactone) revisited. (November 2016) - Phillipson, Kate; Jenkins, Michael J.; Hay, James N.
Graphical abstract: Crystallinity = Primary + Secondary Xt  = X∞ (1 − exp (−Zt n ) (1 + ks t 1/2 ) Highlights: The Avrami equation has been modified to incorporate secondary crystallization. The presence of secondary crystallization accounts for fractional constant n values. Secondary crystallization develops with the square root of time involving diffusion of small segments of the chain. Primary crystallization involves the linear growth of lamellae with time involving long entangled chain segments. Abstract: It is suggested that the overlap of primary and secondary crystallization is a cause of the repeated observation of non-integer n values in polymer crystallization. The possibility that two concurrent crystallization processes occurring during the crystallization of poly (є-caprolactone), and polymers in general, may account for anomalous fractional values of the Avrami exponent, of no theoretical significance, is reconsidered using data from the recent evaluation of the kinetics of crystallization which placed emphasis on evaluating the secondary crystallization stage. In general constant n values in excess of that expected for the crystallization mechanisms could readily be interpreted in terms of the additional crystallinity developed by the secondary process and these values increased commensurate with the rate constant of secondary crystallization.